Welcome to the 5th Volume of the Open Journal of Circuits and Systems - Nicole McFarlane (IEEE Open Journal of Circuits and Systems, 2024)
Welcome to the 5th volume of the Open Journal of Circuits and Systems (OJCAS). The Circuits and Systems Society’s Gold Open Access Journal is maturing, welcoming more submissions and getting our first impact factor score. I welcome our new Associate Editor in Chief, Alex James of Digital University Kerala in Trivandrum India to help mature the journal even more. As the journal matures, it is important to note that OJCAS covers all the topics of the society with the only exception being that it is open access. This means we hold submissions to the same quality standard as the other IEEE Journals. As soon as the paper is accepted, the paper is immediately available on IEEE Xplore and freely available to all researchers across the globe. In order to cover the cost of hosting the papers, as well as minimal editing and formatting, the article processing charges are indeed higher than traditional journals. Fortunately, many institutions have open access funds to cover this purpose and some funding agencies in certain countries mandate that research funded by those agencies be freely available to the public. In addition, IEEE has a waiver policy for authors from low and lower-middle income countries. More facts about open access for IEEE can be found at https://open.ieee.org/about/faqs/.